Effects of Water Stress on Growth and Aspects of Primary Metabolism of Seedlings of Zea Mays Linn. Variety Farz 27. - Ebukanson, Gabriel John (Obafemi Awolowo University, 2014)
Maize seedlings raised for six days were subjected to water stress treatments at 76.6% relative water content (RWC) and 66.5% RWC with appropriate controls.